Everyday makers of international law : from great halls to back rooms - Soave, Tommaso (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"Part essay, part novel, this book offers a unique take on the inner workings of international courts. It reveals how judges reach their decisions and what invisible actors (counsel, advisors, bureaucrats, academics) contribute to the process. The narrative combines the author's first-hand experience with rigorous research in legal sociology"--
Preface: Any resemblance is purely intentional -- Carnegieplein 2, 10:00 AM -- Coffee, cigarettes, and international judicial practices -- A new generation of litigators -- Telling a story -- The invisible army -- The three wise monkeys -- The lyophilization of life -- The memo -- To capture the world -- Bricolage -- The explorer -- A four-letter word -- What does it mean... -- The stage -- The moment of (constructed) truth -- Truth woven together -- Spijkermakersstraat 9, 8:00 PM.
Includes bibliographical references and index.
Keywords: International courts; Judicial process; International law; Judicial procedure; Judicial system; International courts; International law; Lawyers; Courts of justice; International courts; International law; Judicial process